DIVERSITY OF ANTIPYRETIC PLANTS IN PURWOREJO REGENCY, CENTRAL JAVA PROVINCE, INDONESIA - Slamet Mardiyanto Rahayu; Wahyu Aprilyaningsih (Nusantara Hasana Journal, 2026)
This study investigates the diversity of antipyretic plants traditionally utilized by local communities in Purworejo Regency, with a particular focus on Guyangan Village. Employing an ethnobotanical approach that integrates field observation, semi-structured interviews, and taxonomic identification, the research documents plant species used in the management of fever and analyzes associated traditional knowledge. The findings reveal that five plant species are commonly employed as antipyretic remedies: Annona muricata, Bryophyllum pinnatum, Curcuma xanthorrhiza, Moringa oleifera, and Zingiber officinale. These species are utilized in various preparation forms, reflecting localized knowledge systems and adaptive healthcare practices. The study highlights the importance of preserving ethnomedicinal knowledge while providing baseline data to support future phytochemical, pharmacological, and conservation research initiatives in Central Java.